Sintesis Papan Komposit Serat Bambu Apus dan Serbuk Kayu Jati dengan Metode Hot Press untuk Aplikasi Door Trim Mobil - Silviana Simbolon; Silviana Simbolon (Program Studi Teknik Kimia, Universitas Pamulang, 2022)
Research has been carried out on composites from apus bamboo fiber and teak wood particles for car door trim applications. The research method used is compression molding using a hot press machine and testing is based on ISO 527-2 & ASTM D790 standards. This analysis uses the independent variable, namely the ratio of the volume fraction of apus bamboo fiber and teak wood particles 10:30, 20:20, 30:10%. While the fixed variables are 60% epoxy volume fraction, hot press temperature 100°C, pressing load 30 psi, and for 20 minutes. From the tensile test data, it is found that the variation of 30:10% fiber and particles which the variation with the best result is 84.69 MPa, then followed by a variation of 20:20%, is 42.60 MPa. The two variations above the minimum standard value of high-density fiberboard SNI 01-4449-2006:5-9 is 35 MPa. While the variation of 10:30% gets a value of 21.61 MPa which is below the minimum standard. For the bending test, the variation of 30:10% is the variation with the best result, which is 60.24 MPa and is above the minimum standard. Meanwhile, the variation of 10:30% and 20:20% has the lowest bending strength value with a value of 15.43 MPa and 29.61 MPa and is still below the minimum standard that has been set. For the fracture surface results, all variations resulted in fiber pull-out failure but the 30:10% variation which has ductile fracture properties and is considered safer for car door trim applications.